Low Levels of Sex Hormone-Binding Globulin Constitute an Independent Risk Factor for Arterial Stiffness in Korean Women - Kunhee Han; Hyejin Chun; Moon-Jong Kim; Doo-Yeoun Cho; Soo-Hyun Lee; Bo Youn Won; Kwang-Min Kim; Nam-Seok Joo; Young-Sang Kim (International Journal of Endocrinology)
The association between sex hormone-binding globulin (SHBG) and arterial stiffness in women is not conclusive. In addition, obesity might also be involved in the relationship between SHBG and atherosclerosis. The aim of this study was to determine the relationship between SHBG and arterial stiffness in association with central obesity in women. This cross-sectional study included 381 women who participated in the health checkup programs in one hospital. The brachial-ankle pulse wave velocity (baPWV) was measured as a marker for arterial stiffness. A negative correlation was observed between SHBG levels and baPWV (rho = −0.281). The relationship was significant even after adjusting for potential confounders (beta = −0.087 in fully adjusted model). After considering the interaction between central obesity and SHBG levels, the significant association was evident only in obese women (P for interaction = 0.025). Adjustment for a 10-year atherosclerotic cardiovascular disease (ASCVD) risk scores, instead of each cardiovascular risk factor individually, did not affect the significance of the relationship between SHBG levels and baPWV. Serum levels of SHBG were negatively associated with arterial stiffness independent of cardiovascular risk factors or 10-year ASCVD risk scores in Korean women. The relationship may be potentiated by central obesity.